Temperature extremes in the Argentina central region and their monthly relationship with the mean circulation and ENSO phases. (20th October 2016) - Rusticucci, Matilde; Barrucand, Mariana; Collazo, Soledad
ABSTRACT: The aim of this study is to analyse the interannual variability of monthly climatic indices of extreme daily temperature in the central‐north region of Argentina throughout a year and its relationship with the atmospheric circulation. The impact of El Niño‐Southern Oscillation (ENSO) over different temperature indices throughout the year is specially analysed. Globally used indices in the 1970–2010 period are utilized for this purpose. The trends of temperature extremes show warming conditions in several months, especially in October and November. In order to find possible forcings of extreme temperature in the region at monthly scale, the co‐variability with other circulation monthly time series such as changes in the intensity of Southern Hemisphere semi‐permanent anticyclones and the intensity of the subtropical jet were studied. The main finding was a systematic shift of the South Atlantic anticyclone towards the west over the decades in June and August, which might hinder the cold advections over the region surveyed. Moreover, the influence of the variation on the intensity of the subtropical jet over extreme events showed significant positive (negative) correlations between the intensity of the jet and the frequency of cold (warm) indices in a great number of months. Finally, the influence of the ENSO phases on each of the temperature extremes analysed was studied. It was found that under El Niño conditions, minimum temperatures are affected quite evenly throughout the year, fostering the occurrence of warm nights. The impact of the El Niño event on the maximum extreme temperatures, however, shows seasonal differences. Between July and September warm days conditions are fostered, while between November and February the opposite (cold days) can be seen. This results in a decrease in the temperature range in the region surveyed during the summer months under El Niño conditions.